Pemberdayaan Peternak Cerdas Iklim Melalui Teknologi Pakan Silase Berbasis Pakan Lokal di CV. Muda Bakti Barokah Farm Sebagai Upaya Peningkatan Produksi Susu Kambing - Noersidiq, Azhary; Fahrullah, Fahrullah; Dewi Mandalika, Eka Nurminda (Universitas Mataram, 2025)
The concept of a climate-smart farmer refers to farmers who can adapt and innovate in response to climate change by applying appropriate technology, managing feed efficiently, and utilizing local resources sustainably. In line with this concept, this community service activity was carried out at CV. Muda Bakti Barokah (MBB) Farm, Lelong Village, Central Lombok, West Nusa Tenggara, which is a center for dairy goat farming and a pioneer in the use of local feed resources. The program aimed to address feed availability issues and low milk production caused by dependence on seasonal fresh forage. Activities included training and hands-on practice in producing silage using local ingredients such as corn stover, leucaena leaves, odot grass, rice bran, molasses, mineral mix, and SBP (Saus Burger Pakan) fermentor, formulated to contain 12% crude protein and 60% total digestible nutrients (TDN). The results showed an increase in farmers’ understanding up to 95% regarding the benefits of silage as well as their technical skills in preparing and providing fermented feed. The silage produced had a fresh acidic aroma, yellowish-green color, and soft texture, indicating optimal fermentation and making it suitable as basal feed for dairy goats. The application of this silage technology is expected to ensure year-round feed availability, improve nutrient digestibility, and sustainably enhance goat milk production, while fostering climate-smart farmers who are adaptive to seasonal changes.